(untitled) (Educação e Pesquisa, 2005)
With the purpose of drawing a historical picture of the education and action of teachers in the State of São Paulo countryside, this article sketches what we have called a "rustic" (Mathematical) Education, making use of an adjective already in use in Sociology. The term 'decentering', borrowed from Hall (2004), is used here to intensify a feature of the present study, namely, its intention of freeing itself from the more usual approaches, both in the History of Education and in the History of Mathematical Education, which take as their point of departure the big centers and 'classical' institutes of education (for instance, the Faculties of Philosophy), neglecting a plurality of aspects that, we believe, are essential to understand more widely and globally certain educational practices. To realize such intention we start from a characterization of the rural education system, and then situate the movement of expansion of the secondary education, whose apex takes place in the 1950s with the construction of schools and the need to train teachers to work in them. Although the region around Bauru (SP) is the focus here, it can be seen that the understanding emerged here can characterize other contexts. Finally, we discuss the Nova Alta Paulista, a region of more recent occupation, thereby configuring a movement of exchange between the State's older regions on one side, with their well-established institutions, and the 'new' regions on the other, allowing a glimpse of a kind of extended concept of colonization, now applied to the educational context.